THE EFFECTS OF CHARCOAL FROM DIFFERENT AGRICULTURAL WASTES IN REDUCING ETHYLENE PRODUCTION OF BERANGAN BANANA (Musa sp. AAA Berangan) - Nor Afifah A.R.; Siti Amirah M.Z.; Husni Hayati M.R.; Wan Zaliha W.S (UNEJ e-Proceeding, 2017)
Banana is a climacteric fruit, it produces enough ethylene bringing about speedy changes inphysico-chemical characteristics, including colour, texture, aroma, chemical composition,respiration rate and senescence. Ethylene, a colourless gas, is the main regulator of ripeningin climacteric fruits which leads to the short marketable life and increase postharvest losses.These losses can be reduced by adopting various postharvest management practices that arecurrently in practice all over the world. One of the most effective ethylene removals ispotassium permanganate. However, the usage of non-commercial charcoal from agriculturalwastes that capable to remove or absorb ethylene such as palm kernel shell (PKS), sugarcanebagasse (SB) and coconut shell (CS) is scarce. The treatments were i) control (withoutethylene absorbent), ii) 25g PKS, iii) 25g CS, and iv) 50g SB charcoal with 3 replications. Thepostharvest parameters assessment were internal ethylene production, fruit colour indices,firmness, titratable acidity (TA), soluble solids concentration (SSC), weight loss and starchpattern index (SPI). Internal ethylene production was assessed on daily basis. Meanwhile,other quality parameters were assessed on every four days interval. PKS had the ability todelay the climacteric peak of the ethylene production and prolong the shelf life of Beranganbanana, without significant reduction in its postharvest quality. In addition, PKS charcoalwere light, easy to obtain and cheaper ethylene adsorbent. In contrast, SB charcoal was lesseffective in delaying the ripening of Berangan banana. The shelf life of Berangan banana canbe extended up to 6 days with no apparent changes in colour and weight loss.